Evaluating alternative resource allocation in an emergency department using discrete event simulation. (December 2016) - Bedoya-Valencia, Leonardo; Kirac, Emre
Reducing emergency department (ED) overcrowding in the hope of improving the ED's operational efficiency and healthcare delivery is an important objective for healthcare providers. This research analyzes resource allocation with the objective of reducing patient length-of-stay (LOS) and time to be seen by a physician or physician assistant (TBSPPA) while leveling resource utilization. Different levels of resources (physicians, physician assistants, and nurses) were changed in controlled experiments in order to analyze patients' LOS and TBSPPA, as well as resource utilization. The experiments were performed using a simulation model based on data from an ED at a local hospital. The simulation model accounts for patients with different severity levels as well as different rates for patient arrivals. Based on the severity, patients are treated by combinations of multiple resources, often with interspersed waiting time. Results indicate that the simulation model can be used as a tool to help decision makers in the ED with the allocation of resources. The experiments show an average reduction of 14% in the average patients' LOS, 16% in the average patients' TBSPPA, and leveled resource utilization between 70% and 80% when allowing a restructure of the ED resource capacities.